Śrī guru sārvabhauma - Krṣṇarāv, Ji. Es (SAMP early 20th-century Indian books project ;, 1946)
Biography of Rāghavendra Swami, 1601-1661, Hindu religious leader and exponent of Dvaita school in Indian philosophy.